Conceptos y consideraciones generales sobre la traducción - Abood, Sroor; Mohesan, Mohamed (Al-Adab Journal, 2023)
Translation is important in every society in the world, because it destroys language barriers between countries. Through translation we can communicate with others despite the difference in languages. The translation activity is a tool to solve communication problems and build bridges between heterogeneous cultural groups, which react to different social, religious, historical circumstances, etc. For this reason, translation has a communicative objective, which allows overcoming the obstacles established by the cultural linguistic differences found between the interlocutors. This study shows basic concepts about the translation process such as its classes, its strategies, its competencies, as well as the errors that are made when translating from one language to another.